"Bacillus mediterraneensis, " a new bacterial species isolated from human gut microbiota. (July 2016) - Alou, M.T.; Fournier, P.-E.; Raoult, D.
Abstract: We present a brief description of "Bacillus mediterraneensis" strain Marseille-P2366 T (= CSUR P2366 = DSM 102091), a new species isolated from the gastrointestinal tract of a healthy 13-month-old boy from Senegal.